Fostering sustainable global dialogue with Africa and its diaspora : case of the Caribbean (Govt of Barbados BridgetownBB, 2007)
Provides information on the goal, background, origin and objectives of the Conference. Includes programme for the 2007 conference.
Keywords: CULTURAL RELATIONS